Identification of the assets of a tourist destination from the point of view of residents (Journal of Economic Research & Business Administration, 2022)
The process of brand formation during its viability began with goods and services and continued in the marketing of states. The formation of national brand by the states has acquired a sectoral character. Including the creation of a tourist brand, due to the accelerated pace of tourism development, is undoubtedly a prerequisite for the development of tourism in the country. And the development of tourism in the country, in turn, is the influx of sustainable economic development. In this regard, with the scale of the territory and the variety of natural resources of the states, we recommend destination branding as an important component of regional development. Taking into account the above-mentioned substantiations, we set the definition of tourist destination assets as a prerequisite for the formation of destination brand as the goal of the research. In particular, the purpose of the study is to determine the areas of recreation and additional activities recognized as attractive in the tourist destination of Almaty region. A survey was conducted on the nature of the brand of the Almaty region as a tourist destination. Determination of destination assets was carried out from the point of view of application of the population's ambassadorial activities. According to the results of the research, attractive recreation destinations and types of additional services, focused on the stakeholders of the destination, were proposed. In particular, types of active recreation are recognized as the most attractive areas of recreation by the population, and the observance of safety measures are defined as mandatory additional services.Keywords: destination, branding, additional services, population, destination assets, natural resources.